2020
DOI: 10.1177/0300060520939370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cranial electrotherapy stimulation on preoperative anxiety and blood pressure during anesthetic induction in patients with essential hypertension

Abstract: Objective Cranial electrotherapy stimulation (CES) is a non-invasive treatment that improves symptoms such as anxiety and pain. The purpose of this study was to analyze the effect of CES pretreatment on levels of preoperative anxiety, pain, and hemodynamic responses—especially changes in blood pressure—during anesthetic induction in patients with essential hypertension. Methods Eighty patients undergoing general anesthesia were randomly assigned to receive either no pretreatment (control group, n = 40) or CES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Since the discovery of electricity, it has been known that electricity stimulates nerve fibers and induce muscle contractions during physiotherapy, and low and medium waveforms can be produced by varying the frequency of the electrical current. The effect of electrical stimulation on muscles enhances local metabolism, increases neuromuscular excitability and motor neurons, promotes the growth and germination of axons and neuromuscular junction regeneration [ 59 ], thus repairs and rebuilds the damaged or atrophied denervated skeletal muscles, and improves muscle quality and strength [ 15 , 60 62 ]. Blickenstorfer and Kampe reported that the application of electrical stimulation to some skeletal muscles could induce brain plasticity of the pain-associated sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of electricity, it has been known that electricity stimulates nerve fibers and induce muscle contractions during physiotherapy, and low and medium waveforms can be produced by varying the frequency of the electrical current. The effect of electrical stimulation on muscles enhances local metabolism, increases neuromuscular excitability and motor neurons, promotes the growth and germination of axons and neuromuscular junction regeneration [ 59 ], thus repairs and rebuilds the damaged or atrophied denervated skeletal muscles, and improves muscle quality and strength [ 15 , 60 62 ]. Blickenstorfer and Kampe reported that the application of electrical stimulation to some skeletal muscles could induce brain plasticity of the pain-associated sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The exciting effect on the muscle can enhance the local metabolism, and adaptation is avoided by the application of multiple waves. 16 , 17 Neuromuscular electrical stimulation on the basis of functional exercise can increase muscle strength and improve limb asymmetry after ACL reconstruction. However, the optimal electrical stimulation frequency varies with the treatment target.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effectiveness of CES in anxiety treatment has been proven successful [ 165 , 166 ]. Furthermore, this method also can be used in the pretreatment of preoperative anxiety [ 167 ].…”
Section: Brain Stimulation Methods For Chronic Painmentioning
confidence: 99%